Evidence on the Nature of Audit Planning Problem Representations: An Examination of Auditor Free Recalls - Christ, Mary York (The Accounting Review, 1993)
[Audit planning is a crucial task in the audit process. While making planning decisions, auditors have a large amount of information available to them and their existing knowledge structures influence how this information is used to form a problem representation. This problem representation has a significant effect on all subsequent decision making. The purpose of this study is to investigate the nature and evolution of auditors' planning problem representations by an examination of free recalls. In the cognitive psychology literature, it has been reported that, as decision makers accumulate more experience, their knowledge structures change to embody more total knowledge, more knowledge of relationships, and more abstract knowledge. In the context of an audit planning task, I predicted that problem representations formed by more experienced auditors would reflect these characteristics. To test the hypotheses, an experimental study was conducted with 211 practicing auditors. Subjects were from 16 offices of the then Big Eight public accounting firms, with experience levels ranging from one month to 30 years. Using experimental materials that consisted of approximately 20 pages of background information on a hypothetical audit client, subjects completed a planning task, followed by a background questionnaire, and a surprise recall task. The free recalls provide indirect evidence on the nature of the problem representations formed during the planning task. The results suggest that the problem representations of managers and partners may be different from those of seniors or juniors. The manager/partner recalls included a smaller percentage of simple case facts and a higher number and percentage of abstractions from the basic facts. These results have potential implications for audit practice. To the extent that the managers and partners form "better" problem representations and are actively involved in the process, more effective and efficient audit planning might be possible. However, more research needs to be conducted to determine the specific effect of the exhibited differences on planning decisions.]